(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Obesity, a multifactorial disorder characterized by excessive accumulation of adipose tissue, poses a global health burden with significant implications for metabolic, cardiovascular and endocrine systems. While conventional approaches focus on calorie restriction and pharmacological interventions, they often fall short due to individual variability, poor sustainability and inadequate attention to systemic imbalances. Ayurveda, the traditional Indian system of medicine, offers a comprehensive and individualized approach to obesity, conceptualized as Sthaulya, a condition primarily involving Kapha Dosha imbalance, Medodhatu accumulation along with impaired Agni (digestive/metabolic fire). This pathophysiological model highlights the interplay between digestion, metabolism, tissue nourishment and psychosomatic factors. Ayurvedic dietary principles emphasize the consumption of Laghu (light), Ruksha (dry) and Ushna (hot) foods, alongside mindful eating practices and metabolic-enhancing spices, aligning with modern concepts of glycemic control, gut health and circadian eating. Treatment strategies include Shodhana (detoxification), Shamana (palliation) and lifestyle interventions (Vyayama, Dinacharya), supplemented by potent herbal and mineral formulations. Key agents such as Guggulu, Loha Bhasma, Shilajatu, Guduchi, Musta and Triphala exert anti-obesity, anti-inflammatory and metabolic regulatory effects while supporting sectional nutrition-the targeted nourishment of specific tissues and organ systems compromised in obesity. By addressing the root causes and maintaining systemic harmony, Ayurveda provides a sustainable framework for obesity management. Integrating traditional Ayurvedic wisdom with modern nutritional and biomedical sciences offers a promising path toward personalized, holistic and long-term solutions for the obesity epidemic.